Periodontitis and bone metabolism in patients with advanced heart failure and after heart transplantation. (1st March 2017) - Schulze‐Späte, Ulrike; Mizani, Iman; Salaverry, Kristina Rodriguez; Chang, Jaime; Wu, Christina; Jones, Meaghan; Kennel, Peter J.; Brunjes, Danielle L.; Choo, Tse‐Hwei; Kato, Tomoko S.; Mancini, Donna; Grbic, John; et al.
Abstract: Aims: Heart failure (HF) is a multiorgan, pro‐inflammatory syndrome that impairs bone metabolism. Pro‐inflammatory cytokines and bone catabolism enhance periodontal disease, a local inflammatory, bacteria‐induced disease that causes bone loss and periodontal soft tissue destruction. Methods and results: Medical and dental examinations were performed on patients with HF ( n = 39), following heart transplantation (post‐HTx, n = 38) and controls ( n = 32). Blood, saliva, and gingival crevicular fluid were analysed for bone metabolism and inflammation markers. HF average New York Heart Association classification was III. Average time since HTx was 1414 days. Pro‐inflammatory tumour necrosis factor‐alpha was higher in HF and HTx as compared with controls ( P < 0.05). Both HF and HTx participants had higher levels of bone resorption marker C‐terminal telopeptide and parathyroid hormone with subjects in the HF group having the highest serum levels of all groups ( P ≤ 0.05). In contrast, 25‐hydroxyvitamin D was lowest in HF. HF patients had greater clinical attachment loss, cumulative pockets depth (greater than 3 mm) and probing depth ( P < 0.05) as compared with controls. Cumulative pockets depth correlated significantly with measures of the inflammatory burden, β‐glucuronidase in saliva ( r = 0.4863, P < 0.01), interleukin‐1b in saliva ( r = 0.5149, P < 0.01), and gingival crevicular fluid ( r = 0.6056, P < 0.001) in HF. However, adjustment of periodontal results for measures of oral hygiene (plaque, bleeding on probing), systemic 25‐hydroxyvitamin D, and race attenuated significant differences between groups. Conclusions: Patients with HF exhibit more severe periodontal disease associated with increased bone turnover markers when compared with control patients. However, local and systemic factors may account for this association and should be evaluated in future studies.